Dendrites‐Free Zn Metal Anodes Enabled by an Artificial Protective Layer Filled with 2D Anionic Nanosheets. Issue 10 (22nd August 2021) - Zhang, Ying; Zhu, Ming; Wang, Guanyao; Du, Fei‐Hu; Yu, Fangfang; Wu, Kuan; Wu, Minghong; Dou, Shi‐Xue; Liu, Hua‐Kun; Wu, Chao
Abstract: Metallic zinc (Zn) has been considered to be an ideal anode material for aqueous batteries, but is impeded by the growth of Zn dendrites and its side reactions with an aqueous electrolyte. Here, it is reported that an artificial protective layer filled with novel 2D Zn 2+ adsorbed Sb3 P2 O14 3− (denoted as Zn‐Sb3 P2 O14 ) nanosheets provide an effective route to mitigate the above challenging problems. The Zn‐Sb3 P2 O14 protection layer not only avoids the direct contact with the aqueous electrolyte to suppress the side reactions but also allows for Zn‐ions to pass through the protection layer rapidly. Moreover, the 2D Sb3 P2 O14 3− skeleton with negative charge also confines the 2D diffusion of Zn‐ion along the lateral surface of Zn anode, resulting in a uniform electron‐deposition. This unique protection layer not only enables dendrite‐free Zn plating/stripping with an average Coulombic efficiency of 99.2% for 200 cycles, but also sustains the symmetric Zn||Zn cell over 1300 h at 1 mA cm −2 and 1 mAh cm −2 as well as for 450 h at 10 mA cm −2 and 10 mAh cm −2 . Such advantages bring high reversibility to full Zn batteries with MnO2 cathodes, which deliver a discharge capacity of 111.7 mAh g −1 after 1000 cycles. Abstract : An artificial protective layer filled with novel 2D Zn 2+ adsorbed Sb3 P2 O14 3− nanosheets offer a very effective way to mitigate the Zn anode‐associated challenges including the growth of Zn dendrites and the side reactions between Zn and electrolyte, leading to an excellent electrochemical performance in terms of high reversibility and cycling stability.